2014
DOI: 10.1057/jphp.2014.30
|View full text |Cite
|
Sign up to set email alerts
|

Building capacities of elected national representatives to interpret and to use evidence for health-related policy decisions: A case study from Botswana

Abstract: Elected national representatives make decisions to fund health programmes, but may lack skills to interpret evidence on health-related topics. In 2011, we surveyed the 61 members of Botswana's Parliament about their use of epidemiological evidence, then provided two half-days of training about using evidence. We included the importance of counter-factual evidence, the number needed to treat, and unit costs of interventions. A further session in 2012 covered evidence about the HIV epidemic in Botswana and plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In some LMICs large amounts of data are collected in the form of national health surveys, program monitoring data and operational research [ 12 , 50 , 51 , 71 ], creating a reservoir of potential ‘valuable’ local evidence for decision-making. However, the use of this data is limited by low levels of capacity to analyse it for dissemination for policy and practice [ 12 , 53 , 72 ] and issues of data quality [ 30 , 41 , 53 , 73 ], hence the description “data rich, information poor” ([ 12 ], p.S4). Policymakers lament the difficulty in accessing relevant research findings that are of high quality and in digestible formats and they often have limited skills in interpreting evidence [ 30 , 41 , 53 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some LMICs large amounts of data are collected in the form of national health surveys, program monitoring data and operational research [ 12 , 50 , 51 , 71 ], creating a reservoir of potential ‘valuable’ local evidence for decision-making. However, the use of this data is limited by low levels of capacity to analyse it for dissemination for policy and practice [ 12 , 53 , 72 ] and issues of data quality [ 30 , 41 , 53 , 73 ], hence the description “data rich, information poor” ([ 12 ], p.S4). Policymakers lament the difficulty in accessing relevant research findings that are of high quality and in digestible formats and they often have limited skills in interpreting evidence [ 30 , 41 , 53 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of this data is limited by low levels of capacity to analyse it for dissemination for policy and practice [ 12 , 53 , 72 ] and issues of data quality [ 30 , 41 , 53 , 73 ], hence the description “data rich, information poor” ([ 12 ], p.S4). Policymakers lament the difficulty in accessing relevant research findings that are of high quality and in digestible formats and they often have limited skills in interpreting evidence [ 30 , 41 , 53 , 73 ]. They struggle with being provided an uneven mix of evidence from different sources that is difficult to evaluate, and with being able to ask the right questions for good policymaking [ 41 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Case studies have been used to study various kinds of political and election contexts and have been reported in the literature. Examples include Childs, Webb and Marthaler (2010); (Cockcroft et al 2010); (Bush 2011); (Murray 2010); (Balachandran & Sekar 2013). As is the case in the present study, the aim of this approach is to investigate the factors that affect the phenomenon of interest in one particular contextual setting.…”
Section: Rationale For Using a Case Studymentioning
confidence: 99%
“…While in the Camino Verde trial, SEPA operated almost entirely at the community level, in other instances the approach has been used at the level of planners and policy makers through workshops around evidence presented in the form of summary findings, maps and score cards, not to prescribe solutions but to assist in the interpretation of evidence [41, 46, 47]. …”
Section: Introductionmentioning
confidence: 99%